2014
DOI: 10.1111/vox.12156
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular evidence of a plausible transmission of hepatitis E virus through pooled plasma

Abstract: This work provides, for the first time, indirect evidence of HEV transmission by pooled plasma and warrants further studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 32 publications
0
29
0
2
Order By: Relevance
“…However, an increased prevalence of antibodies was observed in a Japanese study of elderly haemophilia patients who had been treated with non-virus-inactivated clotting factors [198]. Furthermore, it was reported from Canada and France recently that HEV can be transmitted by SD-treated plasma [199,200]. HEV was also transmitted by amotosalen-inactivated plasma in France, which indicates that treatment of plasma with photoactive substances is not able to sufficiently inactivate HEV [201].…”
Section: Recipientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an increased prevalence of antibodies was observed in a Japanese study of elderly haemophilia patients who had been treated with non-virus-inactivated clotting factors [198]. Furthermore, it was reported from Canada and France recently that HEV can be transmitted by SD-treated plasma [199,200]. HEV was also transmitted by amotosalen-inactivated plasma in France, which indicates that treatment of plasma with photoactive substances is not able to sufficiently inactivate HEV [201].…”
Section: Recipientsmentioning
confidence: 99%
“…Plasma donated in the viraemic phase is considered as source of infection by cellular blood components [191,192,193,199]. Other retrospective studies of organ transplant recipients who were multi-transfused and developed hepatitis E after transplantation showed that none of the blood donors was HEV-infected; and therefore donations could be ruled out as source of HEV infection [221].…”
Section: Recipientsmentioning
confidence: 99%
“…Allerdings wurde in einer japanischen Studie bei äl-teren Hämophiliepatienten, die auch mit nicht virusinaktivierten Gerinnungsprä-paraten behandelt worden waren, eine erhöhte Antikörperprävalenz festgestellt [198]. Des Weiteren wurde kürz-lich aus Kanada und Frankreich berichtet, dass HEV durch SD-Plasma übertra-gen werden kann [199,200]. Übertragun-gen von HEV durch Amotosalen-behandeltes Plasma wurden aus Frankreich berichtet, was darauf hinweist, dass eine Behandlung von Plasma mit photoaktivierten Substanzen HEV nicht ausreichend sicher inaktivieren kann [201].…”
Section: Definition Von Ausschlusskriterienunclassified
“…Plasma von virä-mischen Spendern wird nach den vorliegenden Berichten als Infektionsquelle in den zellulären Blutkomponenten angesehen [191][192][193]199]. Retrospektive Untersuchungen von Organtransplantierten, die multitransfundiert wurden und bei denen später eine Hepatitis E diagnostiziert worden war, belegten, dass keiner der Blutspender HEV-infiziert war und die Transfusionen somit als Quelle der HEV-Infektion auszuschließen waren [221].…”
Section: Häufigkeit Der Applikation Sowie Art Und Menge Der Blutprodukteunclassified
“…-A long viremic phase (4-6 weeks with titers up to 10 5 IU/ml) with or without variant clinical symptoms [8]. -Ineffective viral inactivation or reduction [9,10]. -Higher mortality and morbidity in immunosuppressed patients [4].…”
mentioning
confidence: 99%